The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1267/ahc.27.435
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Squamous Cell Carcinoma Antigen, a Serine Protease Inhibitor, in the Integument of Vertebrates: Possible Role in Stratification of Epidermis.

Abstract: Terrestrial vertebrates, particularly eutherian species, show highly stratified epithelium. Recent evidence has indicated that the special organization of the stratification depends largely upon a variety of adhesion molecules, and therefore probably upon some proteases and their inhibitors.The present paper shows the expression of squamous cell carcinoma antigen (SCC antigen), a new serine protease inhibitor, in the integuments of various vertebrate species. In Southern blot analysis, SCC antigen gene was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…SCC antigen was also expressed in the intermediate layer of normal squamous epithelium, indicating that SCC antigen may play an important role in the regulation of squamous stratification [2][3][4]. Recent data demonstrated that the SCC antigen consists of two highly homologous SCC antigen-1 and SCC antigen-2, which belong to the serine proteinase inhibitor (serpin) family [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…SCC antigen was also expressed in the intermediate layer of normal squamous epithelium, indicating that SCC antigen may play an important role in the regulation of squamous stratification [2][3][4]. Recent data demonstrated that the SCC antigen consists of two highly homologous SCC antigen-1 and SCC antigen-2, which belong to the serine proteinase inhibitor (serpin) family [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of the serum SCCA level has been used clinically for the diagnosis and management of cancer of the uterine cervix and some other organs [2][3][4][5][6]. SCCA is also expressed in normal squamous epithelium, and previous reports have indicated that SCCA is closely related with cell differentiation of normal squamous epithelium as well as malignant squamous cells [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SCCA levels begin to increase at 18-20 weeks of pregnancy for the first time when the fetal epidermis begins to cornify during the development of human fetal skins [18]. SCCA genes has been found in most of the eutheria (placental mammals), but not in other vertebrates [19]. Furthermore, several eutherian species show heterogeneous patterns of SCCA nucleotides in Southern blot analyses [19].…”
Section: Role Of Scca In Normal Squamous Epithelial Cellsmentioning
confidence: 99%
“…SCCA genes has been found in most of the eutheria (placental mammals), but not in other vertebrates [19]. Furthermore, several eutherian species show heterogeneous patterns of SCCA nucleotides in Southern blot analyses [19]. This suggests that SCCA has had a role in the stratification and differentiation of integuments during evolutional change.…”
Section: Role Of Scca In Normal Squamous Epithelial Cellsmentioning
confidence: 99%